Coinfection with influenza A(H1N1)pdm09 and dengue virus in fatal cases - Anne Carolinne Bezerra Perdigão; Izabel Letícia Cavalcante Ramalho; Maria Izabel Florindo Guedes; Deborah Nunes Melo Braga; Luciano Pamplona Góes Cavalcanti; Maria Elisabeth Lisboa de Melo; Rafael Montenegro de Carvalho Araújo; Elza Gadelha Lima; Luciene Alexandre Bié da Silva; Lia de Carvalho Araújo; Fernanda Montenegro de Carvalho Araújo (Memorias do Instituto Oswaldo Cruz, 2016)
Abstract We report on four patients with fatal influenza A(H1N1)pdm09 and dengue virus coinfections. Clinical, necropsy and histopathologic findings presented in all cases were characteristic of influenza-dengue coinfections, and all were laboratory-confirmed for both infections. The possibility of influenza and dengue coinfection should be considered in locations where these two viruses’ epidemic periods coincide to avoid fatal outcomes. Dengue is a mosquito-borne viral infection caused by one of the four dengue viruses (DENV-1 to 4). Each of these viruses is capable of causing nonspecific febrile illnesses, classic dengue fever and dengue haemorrhagic fever (Gubler 1998). As a result, dengue is often difficult to diagnose clinically, especially because peak dengue season often coincides with that of other common febrile illnesses in tropical regions (Chacon et al. 2015). In April 2009, a new virus, inﬂuenza A/H1N1/pandemic (FluA/H1N1/09pdm), caused a severe outbreak in Mexico. The virus quickly spread throughout the world, and in June 2009, the World Health Organization declared a pandemic (WHO 2010). In Brazil, the first laboratory confirmed case of FluA/H1N1/09pdm was in July 2009 (Pires Neto et al. 2013). The state of Ceará, in Northeast Brazil, is a dengue endemic area. In this state, the virus influenza A(H1N1)pdm09 has circulated since 2009, and through the first half of 2012, 11 deaths caused by the virus were confirmed (Pires Neto et al. 2013). The influenza and dengue seasons in Ceará overlap, which led to diagnostic difficulties. We report four cases of laboratory-confirmed coinfection of deadly influenza A(H1N1)pdm09 with DENV, which occurred during the dengue and influenza season in 2012 and 2013 in Ceará.